Practices of Planetary Relationality in Colum McCann’s Apeirogon - Goszczyńska, Marta (Text Matters: A Journal of Literature, Theory and Culture, 2023)
For a number of critics, what we are witnessing in postmillennial Anglophone fiction is an attempt to do away with postmodern posturings of ironic distance and ethical non-commitment, and a renewed interest in questions of authenticity, empathy, responsibility and solidarity. According to Christian Moraru, one of the keenest chroniclers of contemporary culture, the shift is rooted in an understanding of the world as an interconnected system of relationality, which the critic discusses under the headings of cosmodernism and planetarity. Moraru locates the premise of this evolving cultural project in its ethical call for “a new togetherness, for a solidarity across political, ethnic, racial, religious, and other boundaries” (Cosmodernism 5), but recognizes it as leaving its imprint on the aesthetic and thematic choices made by contemporary authors. The aim of the paper is to analyze Colum McCann’s 2020 novel, Apeirogon, as indebted to this planetary vision of relationality. In particular, my intention is to trace the impact of this mindset on the narrative structure and the imaginary of the novel.